Adhesion strength of soot particles to cellulose ester membranes determined by centrifuge technique. Issue 2 (1st February 2021) - Almeida, A. F.; Oliveira, W. P.; L. Aguiar, M.
Abstract: Adhesion forces between microparticles and substrates is a parameter of fundamental importance in studies of surfaces contamination and decontamination, filter and surface cleaning, non-contact sampling, and environmental and occupational health assessments. This parameter can be estimated theoretically or determined experimentally. Due to the specificities of the processes, the experimental determination is one of the best choices. Techniques commonly used to determine the particle-substrates adhesion forces include the atomic force microscopy (AFM), electric field detachment method, the aerodynamic detachment, and the centrifuge method. The capability to measure several particles simultaneously; and to determine the adhesion forces of regular and irregular real powders on smooth or rough surfaces in a single experiment, producing statistically reliable results are some advantages attributed to the centrifugation technique. This work aimed to use the centrifuge technique to determine adhesion forces between soot particles and cellulose ester membranes. The effects of the average particles size (11.1 to 29.0 µm), powder consolidation relative centrifuge forces (press-on forces − 63.7, 255.0 and 1, 593.6 RCF), and pore size of cellulose ester membranes (0.2 µm and 0.8 µm) were investigated. Adhesion forces between the soot and cellulose ester membrane substrates were directly affected by the press-on forces, by the average diameter of the soot particles, and by the pore size of the cellulose ester membranes. The theoretical models of Johnson–Kendall–Roberts (JKR) and of Derjaguin-Muller-Toporov (DMT) described the trend of adhesion forces as affected by the soot particle's diameter; although showed high deviation from the experimental data. Copyright © 2020 American Association for Aerosol Research